Interaction forces between nanoparticles in Lennard-Jones (L-J) solvents - Sinha, Indrajit; Mukherjee, Ashim K (Institute of Physics Publishing, 2013)
Molecular simulations, such as Monte Carlo (MC) and molecular dynamics (MD) have been recently used for understanding the forces between colloidal nanoparticles that determine the dispersion and stability of nanoparticle suspensions. Herein we review the current status of research in the area of nanoparticles immersed in L-J solvents. The first study by Shinto et al. used large smooth spheres to depict nanoparticles in L-J and soft sphere solvents. The nanoparticles were held fixed at a particular interparticle distance and only the solvents were allowed to equilibrate. Both Van-der-waals and solvation forces were computed at different but fixed interparticle separation. Later Qin and Fitchthorn improved on this model by considering the nanoparticles as collection of molecules, thus taking into the account the effect of surface roughness of nanoparticles. Although the inter particle distance was fixed, the rotation of such nanoparticles with respect to each other was also investigated. Recently, in keeping with the experimental situation, we modified this model by allowing the nanoparticles to move and rotate freely. Solvophilic, neutral and solvophobic interactions between the solvent atoms and those that make up the nanoparticles were modelled. While neutral and solvophobic nanoparticles coalesce even at intermediate distances, solvophilic nanoparticles are more stable in solution due to the formation of a solvent shield.
Keywords: Interaction forces; nanoparticles; Lennard-Jones (L-J) solvents